2021
DOI: 10.1007/s10393-021-01523-1
|View full text |Cite|
|
Sign up to set email alerts
|

Metabarcoding of Soil Fungi from Different Urban Greenspaces Around Bournemouth in the UK

Abstract: Soil microbes are important for public health. Increasing urbanisation is adversely affecting soil microbiota, which may be contributing to the global rise of immune-related diseases. Fungi are key components of urban environments that can be negatively impacted by altered land-use, land-management and climate change, and are implicated in the development and exacerbation of non-communicable diseases such as allergy, asthma and chronic inflammatory conditions. Fungal metagenomics is building knowledge on fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(125 reference statements)
1
2
0
Order By: Relevance
“…The high biodiversity of the plant endophytic mycobiome from other ecosystems [20,34,79] was corroborated in our study. Metabarcoding resulted in 3821 fungal OTUs distributed heterogeneously among the six host species analyzed.…”
Section: Characterization Of the Endophytic Mycobiome By Edna Metabar...supporting
confidence: 84%
“…The high biodiversity of the plant endophytic mycobiome from other ecosystems [20,34,79] was corroborated in our study. Metabarcoding resulted in 3821 fungal OTUs distributed heterogeneously among the six host species analyzed.…”
Section: Characterization Of the Endophytic Mycobiome By Edna Metabar...supporting
confidence: 84%
“…Lasiosphaeriaceae is the largest and most diverse paraphyletic family in the Sordariales order, containing roughly 30 genera (Huhndorf et al, 2004 ; Marin‐Felix et al, 2020 ). Although the lack of green roof studies with high taxonomic resolution make it difficult to determine whether Lasiosphaeriaceae are common in green roofs, prior research on ground‐level urban soils has shown the presence of Lasiosphaeriaceae (Marczylo et al, 2021 ; Wang, Ma, et al, 2019 ; Zhang et al, 2019 ). The widespread occurrence of Lasiosphaeriaceae suggests that these fungi may become potential green roof specialists over time, but more studies examining the importance of Lasiosphaeriaceae in green roofs and other degraded urban landscapes are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, some soil pathogens were more locally-adapted in human-dominated than natural sites. For example, both the apicomplexan parasites of the family Gregarinomorphea (protist), and some members of the family Pleosporaceae (fungi), which were previously found in green spaces around Bournemouth city (UK) [ 75 ], dominated in urban and suburban sites. This calls for a deeper spatial assortment of pathogens in urban soils to help protecting plants, animals and humans.…”
Section: Discussionmentioning
confidence: 99%